Mean Performance of the Parents and Hybrids for Yield and Yield Contributing Traits in Tomato - Nimit Singh; Ashish Kumar Singh; C.N Ram; R.B Singh; Aastik Jha; Anil Kumar (The Bioscan, 2025)
The present investigation conducted at Acharya Narendra Deva University of Agriculture & Technology, Kumarganj, Ayodhya, during rabi season 2023-24 & 2024-25 to evaluate 67 genotypes (11 parents, 55 hybrids and 1 check variety) in a Randomized Complete Block Design (RBD) with three replications for quantitative traits. Significant genetic variability was observed among hybrids, with several demonstrating early flowering and maturity compared to Kashi Aman. Superior hybrids, including P1×P6, P4×P7, and P6×P7, exhibited remarkable early maturity, improved vegetative growth, and greater fruit numbers per cluster and plant. Hybrids like P4×P7 and P3×P8 showed superior fruit weight and thicker pericarps, enhancing marketability. Highest yields were recorded in hybrids P5×P10, P1×P6, and P4×P7, significantly outperforming the check variety.